Sustainable Finance and Green Bonds: Bridging the Gap Between Protability and Environmental Responsibility - Chairil Afandy; Rizyana Mirda; Suhardy; Rizal Ula Ananta Fauzi; Hatidja, Hatidja; Fachri, Muhammad; Jamaludin, Jamaludin (Asosiasi Ide Bahasa Kepri, 2024)
This study aims to explore the role of sustainable finance and green bonds in bridging the gap between corporate profitability and environmental responsibility. With the increasing global demand for sustainable investment, green bonds are emerging as a financial instrument that allows companies to integrate environmental aspects into their business strategies without sacrificing financial gains. This study uses descriptive analysis methods and case studies to assess the impact of green bonds on the company's financial performance and environment. The results of the study show that investing in green bonds not only drives long-term economic benefits, but also improves the company's image in social and environmental responsibility. These findings underscore the importance of integration between economic benefits and environmental sustainability in the modern financial world.